Exploring Muhadlarah Tradition in Mts Salafiyyah 2: Cultivating Tolerant Islamic Education and Awareness Against Radicalism - Achmad Khusnul Khitam; Zahrotus Sa'idah (BAYAN: Jurnal Studi Islam dan Humaniora, 2026)
This article aims to investigate the tradition of muhadlarah in Mts Salafiyyah Menganti Gresik. It focuses on how this tradition serves as a medium for Mts Salafiyyah students to learn and study Islam as Rahmatan lil 'alamin or Islam for All. By engaging in muhadlarah, students not only deepen their understanding of Islamic teachings but also learn to convey these teachings in a manner that is respectful, non-intimidating, and accessible to diverse audiences. This approach ensures that the values of kindness, tolerance, and universal welfare are integral to their religious education and future endeavors as da'is. This study employs a qualitative method and a sociological communication approach through in-depth interviews with various relevant resources, including the school's headmasters.  This study discovered that the tradition of muhadlarah plays a significant influence in developing students into autonomous individuals and, on the other hand, increasing their eagerness to study Islam as rahmatan lil 'alamin.  It was also discovered that teachers and assatidz play a vital role in directing the  students  to  study  and  understand Islam. In fact, by  conducting this tradition, students have a bigger    enthusiasm    on    reading    books    about    Islam, discussing Islam, and more importantly, attempting to know the danger of radical acts (radicalism) in religious lives and practices.